Automated Spectrophotometric Multi-Pumping Flow System for the Determination of Total Iron in Wine. (21st November 2020) - Andreu, Cristina; Danchana, Kaewta; Cerdà, Víctor
Abstract: A new automated system based on a multi-pumping flow system (MPFS) for the spectrophotometric determination of total iron in various wine samples is presented. This analytical protocol is based on the complex formation between Fe (II) and 2-(5-bromo-2-pyridylazo)-5-(diethylamino)-phenol (Br-PADAP). The addition of ascorbic acid allows the determination of total iron by reducing the Fe (III) present in the samples to Fe (II). Several physical and chemical parameters, including the mixing coil length, the sample volume, the chromogenic reagent concentration, the pH, and the ascorbic acid concentration have been characterized in order to optimize the analytical conditions. The limits of detection and quantification were 34 µg L −1 and 114 µg L −1 respectively. The developed procedure requires minimal sample preparation.